Analisis Kebangkrutan pada Bank Syariah Mandiri Periode 2014-2017 - Fadilla Fadilla (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2019)
The perpose of this reseach is to predict the bankcrupty potency from Sharia Mandiri Banking (BSM). The method that used on this paper is modified altman Z score analysis. This research in 2014-2017 periodes. The altman Z score represents by the net working capital to total asset,retaining earning to total asset, earning before interest and tax to total asset, book value equity to book value of debt. The result showed that BSM fit into safe zone in 2014-2017 periods, because the value of z score are 2014 is 6,26, 2015 is 6,2, 2016 is 6,32, 2017 is 6,37. That values bigger than 2,9.